Frequency of Endometriosis in Women Undergoing Diagnostic Laparoscopy for Subfertility at Sheikh Zayed Hospital Rahim Yar Khan - Saleha Jabeen, Abida Rehman, Nayyer Sultana, Sadia Nazir, Nouman Riaz, Zahid Mahmood, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of endometriosis in women undergoing diagnostic laparoscopy for subfertility. Methods: This cross-sectional study was carried out from 25th February 2019 to 23rd June 2019 at the Department of Obstetrics & Gynaecology, Shaikh Zayed Hospital, Rahim Yar Khan. The sample included 136 patients with subfertility. Patients with diabetes mellitus and hypertension, patients with history of heart diseases and malignancies like breast cancer and brain tumor and severely anemic ladies were excluded. Routine investigations were done. Results: Age range in this study was from 20 to 35 years with mean age of 29.522±1.99 years, mean duration of subfertility 5.058±1.58 years, mean duration of marriage 7.058±1.58 years, mean weight 62.463±6.01 Kg, mean height 1.587±0.07 meters and mean BMI was 24.951±3.45 Kg/m2. 14.7% patients belonged to 20-27 years age group while 85.3% to 28-35 years age group. Endometriosis was seen in 15.4% patients. Conclusion: The couple presenting with unexplained subfertility should be offered diagnostic laparoscopy as endometriosis is a common finding in subfertility even in asymptomatic patients and may adversely affect the fertility rate. Keywords: Subfertility, Diagnostic laparoscopy, Endometrioses